Kualitas Pelayanan Dan Kepuasan Pengguna Jasa Pada PT. Pelabuhan Indonesia IV Cabang Terminal Peti Kemas Makassar - rostini rostini; nursyam nursyam; Nurfadhillah insan maulida (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
PT. Pelabuhan Indonesia IV (Persero) is a state-owned company (BUMN) engaged in port services that provides port facilities and infrastructure in order to support the smooth flow of ships, passenger transportation, and delivery of goods. This study aims to determine the effect of Service Quality on Service User Satisfaction at PT. Pelabuhan Indonesia IV, Makassar Container Terminal Branch. The population in the study at PT. Pelabuhan Indonesia IV (Persero) Makassar Container Terminal Branch 220 Espedisi, namely from the many expeditions that use the services of PT Pelabuhan Indonesia IV (Persero) Makassar Container Terminal Branch. The number of samples is 69 from the existing population. Determination of the number of samples in this study using the Sloving formula. Multiple Linear Regression Analysis Method with a quantitative approach. The results showed that reliability, responsiveness, assurance, empathy, tangible, simultaneously affect service user satisfaction. Meanwhile, through partial, reliability, responsiveness, assurance, empathy, tangible all have a positive effect, but only responsiveness and empathy have a significant effect.